Juridical Review of Body Shaming Action Through Social Media Based on Positive Law System - Al Hayu Muthoharoh; Siciliya Mardian Yoel; Nur Chasanah (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2022)
This study examines the juridical review of actions of body shaming through social media based on positive legal system. The purpose of this research was to examine in depth about the act of Body Shaming on social media as well as the legal consequences were reviewed from a Positive Law system in Indonesia. The method used in this research was a normative with statue approach. Legal sources used in this research include primary, secondary, and tertiary legal sources. Based on the results of this study, the regulation on the crime of body shaming on social media was stipulated in Article 27 paragraph (3) in the Law of The Republic of Indonesia Number 11 Of 2008 Concerning Electronic Information and Transactions with reference to the elements of contempt / defamation contained in Article 315 of the Criminal Code.